Effect of Annealing Temperature on Structural and Optical Properties of Dip and Spin coated ZnO Thin Films. (2015) - Shivaraj, B.W.; Murthy, H.N. Narasimha; Krishna, M.; Satyanarayana, B.S.
Abstract: This paper reports the influence of annealing temperature on crystalline size, film roughness, surface morphology and photoluminescence properties of ZnO thin films prepared by dip and spin coating techniques. Thin films were annealed at 400 °C and 500 °C for one hour each and their structural properties were studied using XRD, AFM and SEM. The coatings were characterized for photoluminescence using UV-visible Spectrometer. The films produced by both the methods conformed to hexagonal wurtzite structure. The grain size of dip coated films annealed at 400 °C and 500 °C were 291 and 312 nm and for spin coated films were 140 nm and 172 nm respectively. The surface roughness values of the dip coated films corresponding to the two temperatures were 17.31 nm and 23.52 nm and those for spin coated films were 16.74 and 21.43 nm respectively. Annealing temperature significantly influenced crystallinity and surface roughness of the thin films in both methods of coating.